Pengembangan media pembelajaran komik digital berbasis problem based learning pada materi makanan dan sistem pencernaan untuk siswa kelas XI SMA - Beby Rahmawaty Ramadhani; Mariani Natalina Linggasari; Diah Anugrah Dipuja (LPPM Institut Pendidikan Nusantara Global, 2026)
This research develops an interactive digital comic based on Problem Based Learning (PBL) for the topic of Food and the Human Digestive System in Grade XI Biology. Using the ADDIE model, the study was limited to the development phase. The comic, illustrated in Ibis Paint X, arranged in Canva, and published via Flip PDF Professionalwas validated by two biology lecturers and two biology teachers. Limited trials were conducted with 10 biology education students and 20 Grade‑XI learners at SMA Cendana Pekanbaru. Validation and user responses were analysed descriptively. The average expert score was 3.95, while the first and second user trials reached 3.89 and 3.88 on a 4‑point Likert scale, all categorised as 'very good'. The findings indicate that the developed digital comic is highly feasible as a learning medium that visualises abstract digestive concepts, stimulates critical thinking, and increases learner motivation